ANTITUMOR ACTIVITY OF METHANOL EXTRACT OF TEDANIAANHELANS AGAINST EHRLICH ASCITES CARCINOMA IN SWISS ALBINO MICE. - Simpi, Chandraraj; Kalyane, Navanath; Pore, Amol (Asian Journal of Pharmaceutical Research and Development, 2016)
The study was aimed to evaluate antitumor activity of the methanol extract of Tedaniaanhelans against Ehrlich ascites carcinoma in swiss albino mice. In the present study, the methanolic extract of Tedaniaanhelans (MET) was screened for invivo antitumor properties against Ehrlich ascites carcinoma (EAC) tumor bearing mice at 250 and 500 mg/kg body weight doses given orally once daily for 14 days. Results indicated that the administration of extract not only increased the survival of mice with ascites tumor, but also decreased the body weight induced by the tumor burden, viable tissue cell count and reduced packed cell volume. It also altered many hematological parameters during tumor progression indicating the potent antitumor nature of the extract. Among the two doses tested, the 250 mg/kg body weight dose was found to be most potent.